A Pilot Study of Radiculopathy Following Osteoporotic Vertebral Fracture in Elderly Patients: An Algorithmic Approach to Surgical Management. (23rd September 2021) - Lin, Guang-Xun; Sun, Li-Wei; Jhang, Shang-Wun; Ou, Su-Wei; Chang, Kai-Sheng; Tsai, Ru-Yin; Hu, Bao-Shan; Rui, Gang; Chen, Chien-Min
Background: Osteoporotic vertebral compression fractures (OVCF) due to severe and refractory back pain or neurological complications require surgical treatment. In this study, patients with radiculopathy due to foraminal stenosis following OVCF were surgically managed by performing transforaminal full-endoscopic lumbar foraminoplasty and/or discectomy (FELFD).Methods: From May 2015 to November 2019, fifteen patients underwent transforaminal FELFD. Patient data, Charlson comorbidity index (CCI), and American Society of Anesthesiologists (ASA) score were collected. Clinical outcomes, including pre- and postoperative Visual Analog Scale (VAS) scores for back and leg pain, Oswestry Disability Index (ODI), and MacNab criteria of response to surgical treatment, were evaluated.Results: Mean of age, bone mineral density (T-score), CCI, ASA, and follow-up duration were 69.5 ± 6.6 years, −2.6 ± 0.8, 5.2 ± 2.3, 2.4 ± 0.5, and 24.5 ± 8.8 months, respectively. Mean VAS for leg pain significantly decreased from 6.9 ± 0.8 preoperatively to 2.9 ± 1.1 ( P < .05). Mean ODI decreased from 39.9 ± 3.2 preoperatively to 19.3 ± 4.6 postoperatively ( P < .05). The satisfaction rate is 86.7% (based on Macnab criteria), showed six patients had excellent outcomes and seven had good outcomes.Conclusions: Transforaminal FELFD is an effective treatment option for patients with radiculopathy due to lumbar OVCF, including those with severe osteoporosis and elderly patients.